Calibration, testing and application of the AquaCrop model for bean crop under irrigation regimes - da Conceição, Wenderson Nonato Ferreira [UNESP]; de Faria, Rogério Teixeira [UNESP]; Coelho, Anderson Prates [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Dalri, Alexandre Barcellos [UNESP]; de Freitas, Eduardo Pinheiro (Springer Nature, 2024)
Crop growth simulation models relate the soil–water-plant-atmosphere components to estimate the development and yield of plants in different scenarios, enabling the identification of efficient irrigation strategies. The aim of this study was to calibrate crop coefficients for a common bean cultivar (IAPAR 57) and assess the AquaCrop model's efficacy in simulating crop growth under different irrigation regimes (T0 – non-irrigated, T1—fully irrigated, and T2—deficit irrigated) and sowing dates (S1—March 21, S2—April 24, and S3—August 23). Successful calibration was achieved for crop seasons with suitable temperatures to crop growth (S1 and S3). However, during periods with suboptimal temperatures (April 24 season), coupled with reduced irrigation supply (T0 and T2), the AquaCrop model did not appropriately account for the combined effects of thermal and water stresses. Despite adjustments to stress coefficients, this led to an overestimation of crop growth and yield. In long-term simulations, the model successfully replicated the variability of crop water availability over cropping seasons, reflecting the impact of precipitation variations. It recommended irrigation strategies for the study region (irrigate at depletion of 120 and 170% of readily available water for sowing on March 21 and August 24, respectively) to achieve high crop yield (> 2,769 kg ha−1) and water productivity (1,050 to 1,445 kg m−3) with minimal application depths (< 150 mm). While acknowledging the need for improvements in thermal stress calculations, the AquaCrop model demonstrates promising utility in studies and applications where water availability significantly influences crop production.
Keywords: Canopy cover; Crop modeling; Irrigation management; Productivity